Impact of parental leave system on the childbirth plan among working married women: a three-year follow-up study of the Korean longitudinal survey of women and families - Yun Hwa Jung; Yun Seo Jang; Eun-Cheol Park (BMC Pregnancy and Childbirth, 2024)
Abstract Background The Korean government seeks to balance work and family and alleviate low fertility by implementing a parental leave system. This study aimed to identify the impact of the parental leave system on childbirth among married working women in South Korea. Methods This study used three-year follow-up data from the Korean Longitudinal Survey of Women and Families (2016, 2018, and 2020). The number of participants was 324 at baseline. Logistic regressions using a generalized estimating equation model were performed to examine the impact of parental leave on childbirth. Sub-analyses of covariates, childbirth support, and parental leave systems were conducted. Results Of workers covered by the parental leave system, 31.7% considered childbirth. Women covered by parental leave were 3.63 times more likely to plan childbirth (95% confidence interval [CI], 1.32–9.99). The tendency to plan childbirth was pronounced among those in their early 30s (adjusted odds ratio [AOR], 7.20) and those who thought that having children was necessary (AOR, 4.30). Child planning was more influenced by leave support (AOR, 6.61) than subsidies. Conclusions Parental leave systems can have a positive impact on working married women’s childbirth plans. Although this system was effective in a group interested in childbirth, it did not create a fundamental child plan. Time support is more important than money concerning childbirth plans. The parental leave system had an impact on childbirth plan. Appropriate parenting policies can effectively increase the fertility rate.